Promosi Gaya Hidup Sehat Melalui Edukasi Gizi Klinis dan Aktifitas Fisik: Pencegahan Sindrom Metabolik pada Mahasiswa Universitas Sari Mutiara Indonesia - Novita Aryani; Erwin Silitonga; Shely Aulia Putri; Yoel Yonathan Pasaribu; Mian Heldika Ziliwu (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Lifestyle changes among university students, including increased consumption of junk food, sugar-sweetened beverages (SSBs), and low levels of physical activity, have contributed to the growing risk of obesity and metabolic syndrome in young adults. In addition, high academic demands often promote sedentary behavior, further exacerbating these health risks. This community service program aimed to improve students' knowledge and awareness of the importance of balanced nutrition, limiting the intake of junk food and sugar-sweetened beverages, and engaging in regular physical activity as preventive strategies against metabolic syndrome. The program was conducted among 32 first year nursing students from Sari Mutiara Indonesia University using clinical nutrition education, interactive lectures, group discussions, and question-and-answer sessions. Participants' knowledge was evaluated using pre-test and post-test questionnaires. The results showed that the mean knowledge score increased from 57.3 in the pre-test to 80.6 in the post-test, representing a 40.7% improvement. Most participants demonstrated a positive shift in knowledge levels from poor or moderate to good. Furthermore, participants showed a better understanding of the recommended daily sugar intake, the adverse metabolic effects of excessive junk food consumption, and the importance of performing at least 150 minutes of moderate-intensity physical activity per week. These findings indicate that structured clinical nutrition education is effective in improving university students' knowledge and awareness of healthy dietary practices and regular physical activity as preventive measures against metabolic syndrome.